THE INFLUENCE OF PRICE, LOCATION, AND PROMOTION ON BUYING INTEREST: COFFEE NAKO CIBUBUR - Hasanudin; Delia Maretha Puspitasari (SEAN Institute, 2022)
The purpose of this research is to examine how selling aspects like price, place, and promotion influence consumer demand for Nako Cibubur Coffee. This study includes primary and secondary data via questionnaires mailed to 100 participants. Multiple linear regression is the analytical method used. Multiple linear regression analysis demonstrates that pricing has a statistically and practically big positive influence, that location has an effect, and that advertising has an effect on consumers' intentions to make a purchase. Results from this research suggest that Nako Coffee Cibubur's Price, Location, and Promotion may pique the curiosity of customers who already like Nako Coffee because of its quality and taste.